2015
DOI: 10.1007/s00429-015-1040-9
|View full text |Cite
|
Sign up to set email alerts
|

Transgene expression in the Nop-tTA driver line is not inherently restricted to the entorhinal cortex

Abstract: The entorhinal cortex (EC) plays a central role in episodic memory and is among the earliest sites of neurodegeneration and neurofibrillary tangle formation in Alzheimer's disease. Given its importance in memory and dementia, the ability to selectively modulate gene expression or neuronal function in the EC is of widespread interest. To this end, several recent studies have taken advantage of a transgenic line in which the tetracycline transactivator (tTA) was placed under control of the neuropsin (Nop) promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 52 publications
1
46
1
Order By: Relevance
“…The mice developed tauopathy initially in the entorhinal cortex, as expected, but with passing time the abnormalities successively emerged in axonally connected brain areas (de Calignon et al, 2012; Liu et al, 2012). Subsequent studies have found that the tau transgene is weakly expressed in other brain regions, which could influence the pattern of lesion progression (Yetman et al, 2016). However, when considered in light of the orderly neuroanatomic localization of tau lesions in interconnected brain regions in AD (Saper et al, 1987; Arnold et al, 1991; Braak and Braak, 1995), the experiments in mouse models implicate neuronal transport and cytotic mechanisms in the propagation of tau seeds within the nervous system.…”
Section: The Prion-like Properties Of Aggregated Taumentioning
confidence: 99%
“…The mice developed tauopathy initially in the entorhinal cortex, as expected, but with passing time the abnormalities successively emerged in axonally connected brain areas (de Calignon et al, 2012; Liu et al, 2012). Subsequent studies have found that the tau transgene is weakly expressed in other brain regions, which could influence the pattern of lesion progression (Yetman et al, 2016). However, when considered in light of the orderly neuroanatomic localization of tau lesions in interconnected brain regions in AD (Saper et al, 1987; Arnold et al, 1991; Braak and Braak, 1995), the experiments in mouse models implicate neuronal transport and cytotic mechanisms in the propagation of tau seeds within the nervous system.…”
Section: The Prion-like Properties Of Aggregated Taumentioning
confidence: 99%
“…However, while in situ analysis suggested this mouse model only expresses the transgene in the entorhinal cortex (de Calignon et al, 2012), analysis by qPCR of laser-captured dentate gyrus granule cells detected human tau mRNA (Liu et al, 2012). Further, recent work based on tet-induced LacZ expression now indicates that over time the neuropsin promoter activates gene expression fairly widely, including the hippocampus (Yetman et al, 2015). This casts some doubt on the use of this model to definitively test for trans-synaptic propagation.…”
Section: Network Involvement In Trans-synaptic Spread Of Pathologymentioning
confidence: 99%
“…Human mutated APP and human mutated tau tg mice have been crossed to study the interaction of Aβ and tau pathologies [100]. Neurofibrillary tangles are initially found in the entorhinal cortex in tg mice expressing P301L human tau predominantly in that area (rTgTauEC) [135]. With age, tau pathology progresses along connections.…”
Section: In Animalsmentioning
confidence: 99%